2005
DOI: 10.1021/es048166d
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Transformation of Fluoroquinolone Antibacterial Agents and Structurally Related Amines by Manganese Oxide

Abstract: Various members of the popular fluoroquinolone antibacterial agents (FQs) have been frequently detected in municipal wastewater and surface water bodies in recent years. This study was conducted to gain a better understanding of the fate of FQs in the sediment-water environment. Seven FQs were examined for adsorptive and oxidative interactions with delta-MnO2 under environmental conditions and exhibited reactivity in the order of ciprofloxacin approximately enrofloxacin approximately norfloxacin approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
227
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(263 citation statements)
references
References 42 publications
29
227
1
2
Order By: Relevance
“…Figure 9 shows the plot of lnC 0 /C against t where, C represents the concentration of MB at time, t, and C 0 represents the initial concentration of MB. The kinetics of the degradation process fitted to the pseudo-first-order kinetics model well which is in good agreement with the earlier works [12,13,42], where the authors reported the oxidative degradation of a number of organic pollutants with Mn oxides. In the present study, the rate constant (k) was found to be 0.0045 min −1 .…”
Section: Kinetics Of Mb Degradationsupporting
confidence: 90%
See 1 more Smart Citation
“…Figure 9 shows the plot of lnC 0 /C against t where, C represents the concentration of MB at time, t, and C 0 represents the initial concentration of MB. The kinetics of the degradation process fitted to the pseudo-first-order kinetics model well which is in good agreement with the earlier works [12,13,42], where the authors reported the oxidative degradation of a number of organic pollutants with Mn oxides. In the present study, the rate constant (k) was found to be 0.0045 min −1 .…”
Section: Kinetics Of Mb Degradationsupporting
confidence: 90%
“…As manganese (Mn) oxides are powerful oxidants having high-reducing potential, for pollution remediation purpose, land-born natural Mn ores, synthetic nascent state Mn oxides, and materials coated/modified with Mn oxides have been tested as oxidants for degradation of organic pollutants [7,8]. It has already been reported that oxides and hydroxides of Mn 3+ and Mn 4+ can oxidize a variety of natural and xenobiotic organic compounds such as catechol, quinines, substituted phenols, aromatic amines, pesticides, and explosives (e.g., TNT) [9][10][11][12][13]. Trimanganese tetraoxide (Mn 3 O 4 ) is a mixed oxide of Mn containing both di-and tri-valents of Mn.…”
Section: Introductionmentioning
confidence: 99%
“…8), acetic acid, formic acid and oxalic acid, further confirmed the deep oxidation of CIP in Ce(0.48)-OMS-2 suspension. In contrast, only the piperazine moiety of CIP was destructed in MnO 2 suspensions, due to the oxidation of Mn(IV) [32]. The higher oxidation ability of Ce-OMS-2 than MnO 2 indicated the possible existence of other active oxygen species.…”
Section: Pathways Of Cip Degradation In Ce-oms-2 Suspensionmentioning
confidence: 96%
“…18 The ease of formation of N-centered radicals has been reported for a series of chloramines, which play an important role in environmental chemistry and biochemistry. [19][20][21][22][23] Once formed, the N-centered radical 1a can undergo fast protonation yielding the radical cation 1b. The most stable form of 1b adopts a chair conformation of the piperidine ring .…”
Section: Resultsmentioning
confidence: 99%